Cement-based compositions comprising polymer microgels as anti-gas migration agents

By using structured polymer microgels polymerized by reverse phase emulsion in cement, the problem of poor performance of existing anti-gas migration agents under high temperature conditions is solved, and good anti-gas migration performance and safety at any temperature is achieved reduces greenhouse gas emissions and costs.

CN119233955AActive Publication Date: 2024-12-31SNF GRP

Patent Information

Application Number
CN202380038159.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-03
Filing Date
2023-05-02
Publication Date
2024-12-31
Estimated Expiration
2043-05-02

AI Technical Summary

Technical Problem

In the existing cementing technology, although a variety of anti-gas migration agents are used, their effects are limited under high temperature conditions and high concentrations and additional stabilizers are required, resulting in increased costs and poor performance, especially at higher temperatures than At 50℃, the formation of gas channels is still a serious problem and affects safety.

Method used

By introducing such microgel into cement, it improves its anti-gas migration performance during solidification by using structured polymer microgel polymerized in reverse phase emulsion as the anti-gas migration agent in the cement. and reduce the amount of use required.

Benefits of technology

Good gas migration resistance of cement under any temperature conditions is achieved, reducing dependence on other additives, reducing greenhouse gas emissions, and improving the safety and efficiency of the cementing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005115532970000161
    Figure BDA0005115532970000161
  • Figure BDA0005115532970000171
    Figure BDA0005115532970000171
Patent Text Reader

Abstract

The invention relates to the technical field of well cementation, in particular to construction of oil wells and / or gas wells or geothermal energy. More specifically, the subject matter of the present invention is a cementitious composition and an improved well cementation method by introducing a polymeric microgel into the cement as an anti-gas migration agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of well cementing, in particular in the construction of oil and / or gas wells or geothermal energy. More specifically, the subject of the invention is a cement-based composition and an improved well cementing method by introducing a polymer microgel as an anti-gas migration agent into the cement slurry. Background Art

[0002] Cementing involves pumping cement slurry from the surface into the casing and returning it to the surface through the annular space between the casing and the borehole. One of the purposes of cementing is to isolate the different strata through which the well is drilled to prevent the migration of fluids (liquid or gas) between different geological layers or between geological layers and the surface. In particular, from a safety point of view, any gas must be prevented from rising through the annular space between the well wall (borehole) and the casing.

[0003] During the cementing phase, pressurized gas from the subsurface travels through the various formations that the well is drilled and cemented through. This is a critical phase that lasts several hours, during which the cement slurry no longer behaves as a liquid, but has not yet behaved as an impermeable solid. This phenomenon occurs when the cement slurry sets to a point where the hydrostatic pressure of the cement column is insufficient to prevent pressurized gas pockets from propagating through the cement slurry. During the setting process, the gas circulates through the cement column, forming multiple channels in the cement that can reach the surface. This flow of gas can lead to uncontrolled pressure and even explosions, which is why the industry has developed a range of additives to maintain gas tightness throughout the cement setting period.

[0004] Among these additives are latexes, such as natural latex. Such additives have been commonly used in Portland cement since the 1920s, particularly due to the improvement in the mechanical properties of the cement. A decisive improvement occurred in the 1980s when Parcevaux et al. discovered that styrene-butadiene rubber was an effective additive to prevent annular gas migration. This technology was specifically introduced in U.S. Patent No. 4,537,918, which disclosed slag cement compositions in which styrene-butadiene rubber inhibited the escape of gases under pressure in the cement sheath, even at elevated temperatures.

[0005] WO 2012 / 150431 teaches a cementing fluid comprising a polymer suspending agent which may be prepared by an inverse suspension polymerisation process, optionally in an inverse emulsion.

[0006] WO 2004 / 101952 describes a composition for cementing a well.

[0007] US 2015 / 203402 describes a polycarboxylic acid copolymer additive for cement compositions.

[0008] WO 01 / 05365 describes a composition comprising monomeric parts of water-soluble branched or crosslinked amphiphilic polymers.

[0009] WO 2018 / 185037 describes a composition and its use as an agent for controlling the migration of filtrate and / or gas in a fluid injected under pressure into a subterranean formation.

[0010] Although styrene-butadiene rubber based additives are the most commonly used additives to prevent gas migration, these products, while effective, require high concentrations and are relatively expensive. In addition, some products require the use of stabilizers to prevent them from setting in cement, as described in US 4,537,918 and US 4,151,150.

[0011] FR 2704219 introduces a fluid loss control agent with anti-gas migration properties, suitable for oil industry fluids, especially cement slurries. The fluid loss control agent is composed of a polymer obtained by chemically crosslinking polyvinyl alcohol (PVA).

[0012] These fluid loss control agents are water-soluble polymers and their effectiveness is usually limited because some additives cannot be used in high concentrations during the mixing stage due to the high viscosity of the slag. These additives have limited effectiveness in terms of reproducibility, performance and stability, especially at temperatures above 50°C.

[0013] US Patent No. 4,569,395 suggests adding cellulose derivatives (such as hydroxyethyl cellulose) to cement in order to use PVA at temperatures up to 95°C.

[0014] The formation of gas channels is a very serious problem as it can lead to cement embrittlement and problems with surface safety.

[0015] The sheer number of efforts to address this problem speaks volumes about the severity of the problem, which has been a major concern for manufacturers for many years.

[0016] There is still a need for additives that are more effective in making cement non-leaky during the setting process and usable at all temperature conditions without the need for additional additives.

[0017] The inventors unexpectedly discovered that the use of specific microgels can give cement better resistance to gas migration than conventional products. The microgels of the present invention show good performance regardless of temperature conditions, and require much less dosage than prior art solutions.

[0018] The use of the cementitious composition of the present invention is part of the general principle of improving product performance, in particular improving the performance of anti-gas migration agents. The better performance of the polymer microgel according to the present invention can reduce the amount of product required for application, which means that the emission of greenhouse gases (such as carbon dioxide) associated with the manufacture and use of synthetic polymers can be reduced. Summary of the invention

[0019] The present invention relates to a cement-based composition comprising:

[0020] -cement;

[0021] - optionally at least one cement additive;

[0022] - polymer microgels; and

[0023] -water.

[0024] Cementitious compositions may be composed of these compounds.

[0025] In this cementitious composition, the polymer microgel comprises at least one polymer structured by at least one crosslinking agent. The structured polymer is polymerized by at least one monomer in an inverse emulsion (water-in-oil emulsion).

[0026] The invention also relates to a cementing process comprising injecting into the ground a cementitious composition containing a polymer microgel comprising at least one structured polymer obtained by inverse emulsion.

[0027] Description of the invention

[0028] According to the present invention, the term "anti-gas migration agent" refers to an additive capable of limiting gas migration during the setting process of cement.

[0029] Generally speaking, fluid loss control agents can limit the loss of liquid fluids during the fluid loss stage of cementing, such as water loss when in contact with porous areas such as underground clay layers.

[0030] In the literature, the effectiveness of anti-gas migration agents is measured in the same way as the effectiveness of fluid loss control agents. Therefore, people mistakenly believe that fluid loss control agents have anti-gas migration properties. However, while anti-gas migration agents do have the effect of limiting fluid loss, fluid loss control agents do not necessarily have an effect on gas migration. Therefore, measuring the effectiveness of anti-gas migration agents by measuring the amount of fluid loss does not evaluate the effectiveness of anti-gas migration agents.

[0031] To determine the effectiveness of the anti-gas migration agent, a static gel strength analyzer (SGSA) is used. This device measures the static gel strength (SGS) of cement under high temperature and pressure conditions. The instrument is equipped with an internal processor board that sends and receives ultrasonic pulses through the cement paste and then post-processes the data to determine the gel strength in a static medium as a function of time.

[0032] Once the cement slurry is at rest, it develops gel strength, which results in a loss of hydrostatic pressure (the pressure exerted by the cement slurry on the wellbore (borehole) and casing). When the hydrostatic pressure falls below the pore pressure in the drilling area, gas can penetrate and migrate to areas of lower pressure, potentially reaching the surface. During this transition period, the cement slurry is no longer a liquid capable of transmitting hydrostatic pressure, nor is it a solid. The cement slurry now has a gel structure. The gel strength value at which the hydrostatic pressure falls below the pore pressure is called the critical static gel strength (CSGS). As a precaution, the gel strength value at which gas cannot migrate through cement is 239Pa (500lb / 100ft 2 ). Therefore, in general, the transition period between CSGS and 239Pa must be as short as possible to avoid the risk of gas migration. From a regulatory and safety perspective, the transition time must be less than 45 minutes. When the CSGS is at least 100lb / 100ft 2 (100lb / 100ft 2 =0.4788Pa), the slurry begins to gel, and when the CSGS is at least 500lb / 100ft 2 When the gas migration risk ends, the person skilled in the art is familiar with conventional measurement equipment and methods. If necessary, the person skilled in the art can refer to Chapter 5 of Volume 1 of "Fluid Chemistry Drilling and Completion".

[0033] The term "polymer" refers to a homopolymer or a copolymer, wherein a copolymer refers to a polymer prepared from at least two different monomers. Thus, it can be a copolymer of at least two monomers, which can be selected from anionic monomers, cationic monomers, nonionic monomers, zwitterionic monomers and mixtures thereof.

[0034] The term "polymer microgel" refers to the microgels described in the document "Polymer Networks", Chapter 8, pages 227-275. Such polymers are structured polymers that are roughly spherical in shape, with dimensions comparable to the molecular size of linear or branched polymers. A microgel is a microscopic network whose properties depend on its crosslinking density, connectivity, the presence of solvents, etc. Microgels are polymer particles that are insoluble in the medium.

[0035] As used herein, "X and / or Y" means "X" or "Y" or "X and Y".

[0036] The invention also includes all possible combinations of the various disclosed embodiments, regardless of whether these combinations are preferred embodiments or are presented by way of example.

[0037] In addition, when indicating numerical ranges, the limits are also part of these ranges. The disclosure also includes all combinations between the limits of these numerical ranges. For example, a numerical range of 1-20, preferably 5-15, means that the ranges "1-5", "1-15", "5-20" and "15-20" as well as the values ​​1, 5, 15 and 20 are disclosed.

[0038] According to the process of the present invention, cement with better quality can be obtained by selecting the preparation method of the polymer microgel and the chemical composition of the polymer microgel.

[0039] Composition

[0040] The present invention relates to a cement-based composition comprising:

[0041] -cement;

[0042] - optionally at least one cement additive;

[0043] - polymer microgels; and

[0044] -water.

[0045] In the cement-based composition, the polymer microgel comprises at least one structured polymer obtained by polymerization of monomers in an inverse emulsion.

[0046] The cement is preferably selected from pozzolanic materials such as lime based mixtures, silica, alumina, calcium sulfate, Portland cement, ground slag and fly ash and mixtures thereof.

[0047] The cement additives are generally selected from additives commonly used in the application field, including but not limited to dispersants, fluid loss inhibitors, retarders and mixtures thereof.

[0048] Generally speaking, the weight of the polymer microgel in the cementitious composition is preferably between 100 and 100,000 ppm, more preferably between 500 and 50,000 ppm, and most preferably between 500 and 10,000 ppm, relative to the total weight of the cementitious composition.

[0049] The invention also relates to the use of a polymer microgel comprising at least one polymer structured by at least one crosslinking agent for forming a cementitious composition.

[0050] Therein, the structured polymer is obtained by inverse emulsion polymerization of at least one monomer.

[0051] The present invention also relates to a method for preparing a cement-based composition, the composition comprising a mixture of the following compounds:

[0052] - a polymer microgel;

[0053] -cement;

[0054] - Water; and

[0055] - optionally at least one cement additive;

[0056] The polymer microgel contains at least one polymer structured by at least one crosslinking agent,

[0057] The structured polymer is obtained by inverse emulsion polymerization of at least one monomer.

[0058] Polymer microgels

[0059] The polymer microgel is a synthetic polymer microgel. Preferably, it contains a structured polymer polymerized from at least one anionic monomer and / or at least one nonionic monomer and / or at least one cationic monomer and / or at least one zwitterionic monomer and / or at least one hydrophobic monomer. Preferably, these monomers have an unsaturated olefin bond (a double bond between two carbon atoms).

[0060] In another preferred embodiment, the polymer microgel comprises at least one anionic monomer and optionally at least one nonionic monomer.

[0061] Preferably, other anionic monomers that can be used within the scope of the present invention can be selected from a large class of monomers. These monomers can have functional vinyl, particularly acrylic acid, maleic acid, fumaric acid, malonic acid, itaconic acid or allyl. These monomers can also contain carboxylic acid, phosphonic acid, phosphoric acid, sulfonic acid or other anionic groups. Preferably, the monomer belonging to this class is selected from the group consisting of acrylic acid, methacrylic acid, itaconic acid, crotonic acid, maleic acid, fumaric acid, acrylamido undecanoic acid, 3-acrylamido 3-methylbutyric acid, maleic anhydride, 2-acrylamido 2-methylpropane sulfonic acid (ATBS), vinyl sulfonic acid, vinyl phosphonic acid, allyl sulfonic acid, methyl allyl sulfonic acid, methacrylic acid-2-sulfonyl ethyl ester, methacrylic acid sulfopropyl ester, acrylic acid sulfopropyl ester, allyl phosphonic acid, styrene sulfonic acid, 2-acrylamido-2-methylpropane disulfonic acid, and salts thereof, or combinations thereof. Preferred is 2-acrylamido-2-methylpropanesulfonic acid (ATBS) and / or its salts.

[0062] In a special embodiment of the invention, the anionic monomers can be salified (salts).

[0063] The so-called saltization means that at least one acid functional group of the anionic monomer is replaced by a salt that neutralizes the negative charge of the acid functional group. In other words, the non-salified form is equivalent to the acidic form of the monomer, such as the RC(=O)-OH form of the carboxylic acid functional group, while the neutralized form of the monomer is equivalent to RC(=O)-OH - X + In the form of X + Equivalent to a salt with a positive charge. The neutralization of the acid functional groups in the polymer microgel can be partial neutralization or complete neutralization.

[0064] The salified form is preferably a salt of an alkali metal (Li, Na, K, etc.), an alkaline earth metal (Ca, Mg, etc.) or ammonium (such as ammonium ion or tertiary ammonium). The most preferred salt is a sodium salt.

[0065] The salting can be carried out before, during or after the polymerization.

[0066] The content of the anionic monomer in the polymer microgel is preferably between 0 and 100 mol %, more preferably between 20 and 100 mol %, more preferably between 40 and 100 mol %, and more preferably between 50 and 100 mol %.

[0067] The polymer microgel preferably contains at least 30 mol% of anionic monomers, more preferably at least 50 mol%, more preferably at least 70 mol%, more preferably at least 90 mol%, more preferably only anionic monomers. Therefore, the polymer microgel is preferably a polymer of at least one acidic and / or salted anionic monomer.

[0068] In a particular embodiment of the present invention, the polymer microgel preferably comprises 0 to 100 mol % of salified anionic monomers, preferably 0 to 50 mol %.

[0069] In a particular embodiment of the present invention, when the anionic monomer is 2-acrylamido-2-methylpropane sulfonic acid, it is in a hydrated form. The hydrated form of 2-acrylamido-2-methylpropane sulfonic acid is a special form of 2-acrylamido-2-methylpropane sulfonic acid, which can be obtained by controlling the crystallization of 2-acrylamido-2-methylpropane sulfonic acid monomer. US 10,759,746 describes a hydrated form of 2-acrylamido-2-methylpropane sulfonic acid.

[0070] Preferably, the nonionic monomers that can be used in the present invention are selected from the following group: acrylamide, methacrylamide, N-isopropylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, N-hydroxymethylacrylamide, N-vinylformamide (NVF), N-vinylacetamide, N-vinylpyridine and N-vinylpyrrolidone (NVP), N-vinylimidazole, N-vinylcaprolactam, N-vinylsuccinimide, acryloylmorpholine (ACMO), acryloyl chloride, glycidyl methacrylate, glyceryl methacrylate, diacetone acrylamide, hydroxyalkyl (meth) acrylate (C1-C3 alkyl), aminoalkyl (meth) acrylate (C1-C3 alkyl), thioalkyl (meth) acrylate (C1-C3 alkyl), or a combination thereof. Preferably, acrylamide is used.

[0071] The content of the nonionic monomer in the polymer microgel is preferably between 0 and 100 mol %, more preferably between 0 and 80 mol %, more preferably between 0 and 60 mol %, and more preferably between 0 and 50 mol %.

[0072] The content of nonionic monomers in the polymer microgel is preferably less than 70 mol %, more preferably less than 50 mol %, more preferably less than 30 mol %, and more preferably less than 10 mol %.

[0073] Preferably, the cationic monomers that can be used in the present invention can be selected from vinyl type monomers, in particular acrylamide, acrylic acid, allyl or maleic acid monomers with ammonium functional groups (preferably quaternary ammonium). Preferred monomers belonging to this category are selected from the group consisting of quaternized dimethylaminoethyl-acrylate (DMAEA), quaternized dimethylaminoethyl-methacrylate (DEAEMA), dimethyldiallylammonium chloride (DADMAC), acrylamido-propyltrimethyl-ammonium chloride (APTAC), methacrylamido-propyltrimethyl-ammonium chloride (MAPTAC), or a combination thereof.

[0074] The polymer microgel preferably comprises 0 to 100 mol % of the cationic monomer, more preferably 0 to 80 mol %, more preferably 0 to 60 mol %, more preferably 0 to 50 mol %.

[0075] The content of the cationic monomer in the polymer microgel is preferably less than 70 mol %, more preferably less than 50 mol %, more preferably less than 30 mol %, and more preferably less than 10 mol %.

[0076] Those skilled in the art know how to prepare quaternized monomers, for example by R X alkyl halides, where R is an alkyl group (preferably C1-C3) and X is a halogen group (particularly methyl chloride). In addition, the present invention also includes monomers of the DADMAC, APTAC and MAPTAC types, whose halide counterions are fluoride, bromide or iodide instead of chloride.

[0077] The zwitterionic monomers used in the present invention are preferably derived from vinyl units, especially acrylamide, acrylic acid, allyl or maleic acid, and such monomers have amine or ammonium functional groups (preferably quaternary ammonium) and acid functional groups of carboxylic acid (or carboxylate), sulfonic acid (or sulfonate) or phosphoric acid (or phosphate), or a combination thereof. Examples of zwitterionic monomers, such as dimethylaminoethyl acrylate derivatives, such as 2-((2-9(acryloyloxy)ethyl)dimethylamino)ethane-1-sulfonate, can particularly include (but are not limited to): 3-((2-(acryloyloxy)ethyl)dimethylamino)propane-1-sulfonate, 4-((2-(acryloyloxy)ethyl)dimethylamino)butane-1-sulfonate, [2-(acryloyloxy)ethyl](dimethylamino)acetate, dimethylaminoethyl methacrylate derivatives, such as 2-((2-(methacryloyloxy)ethyl)dimethylamino)ethane-1-sulfonate, 3-((2-(methacryloyloxy)ethyl)dimethylamino)propane-1-sulfonate, 4-((2-(methacryloyloxy)ethyl)dimethylamino)butane-1-sulfonate, [2-(acryloyloxy)ethyl](dimethylamino)acetate, [3-(acryloxy)ethyl](dimethylamino)acetate, propyl acrylamidodimethylamino derivatives, for example 2-((3-acrylamidopropyl)dimethylamino)ethane-1-sulfonate, 3-((3-acrylamidopropyl)dimethylamino)propane-1-sulfonate, 4-((3-acrylamidopropyl)dimethylamino)butane-1-sulfonate, [3-(acryloxy)propyl](dimethylamino)acetate, dimethylaminopropyl methacrylamide or derivatives, for example 2-((3-methacrylamidopropyl)dimethylamino)ethane-1-sulfonate, 3-((3-methyldimethylamino)propane-1-sulfonate, 4-((3-methacrylamidopropyl)dimethylamino)butane-1-sulfonate and propyl [3-(methacryloxy)](dimethylamino)acetate and mixtures thereof. FR 3104578 also describes examples of zwitterionic monomers that can be used.

[0078] Preferably, the hydrophobic monomers that can be used in the present invention can be selected from the following groups: 30 Alkyl chain, arylalkyl (C4-C 30 Alkyl, C4-C 30 aryl), propoxylated, ethoxylated, or ethoxylated and propoxylated (meth)acrylate; having C4-C30 Alkyl, propoxylated arylalkyl (C4-C 30 Alkyl, C4-C 30 Aryl), ethoxylated, ethoxylated and propoxylated or di-C4-C 30 (Meth) acrylamide derivatives; alkyl aryl sulfonates (C4-C 30 Alkyl, C4-C 30 Aryl), or having C4-C 30 Alkyl chain, arylalkyl (C4-C 30 Alkyl, C4-C 30 aryl), propoxylated, ethoxylated, or ethoxylated and propoxylated (meth)acrylamide; having C4-C 30 Alkyl, propoxylated arylalkyl (C4-C 30 Alkyl, C4-C 30 aryl), ethoxylated, ethoxylated and propoxylated, or C4-C 30 Dialkyl chain (meth) acrylamide derivatives; alkyl aryl sulfonate (C4-C 30 Alkyl, C4-C 30 In general, the aryl group is preferably C5-C 30 or C6-C 30 .

[0079] Preferably, the content of hydrophobic monomers in the polymer microgel is less than 10 mol%.

[0080] In a particular embodiment of the present invention, the polymer microgel may comprise at least one thermosensitive monomer. By thermosensitive monomer is meant a monomer that changes the physical properties of the polymer as the temperature changes. For example, groups at the lower critical solution temperature (LCST), such as LCST macromonomers, and groups at the upper critical solution temperature (UCST), such as UCST macromonomers, may be mentioned. Those skilled in the art are aware of these types of monomers, which are known and conventional in terms of general knowledge in the art, and those skilled in the art may consult WO 2016162532 if necessary.

[0081] In the process of preparing polymer microgels, the amount of various monomers can be adjusted by professional technicians so that it does not exceed 100 mol%.

[0082] The polymer microgel is structured by at least one crosslinking agent. Preferably, this crosslinking agent is selected from polyethylenic unsaturated monomers (which have at least two unsaturated functional groups), such as vinyl, in particular allyl, propenyl functional groups, or monomers with at least two epoxy functional groups. Examples that may be mentioned are methylenebisacrylamide (MBA), triallylamine, tetraallylammonium chloride, 1,2-dihydroxy-ethyl-bis(N-acrylamide) or (meth)acrylates with multiple functional groups, such as poly(meth)acrylate (ethylene glycol) (PEG-di(meth)acrylate). Preferably, methylenebisacrylamide is used.

[0083] The amount of crosslinking agent is preferably less than 5%, more preferably less than 1%, more preferably less than 0.5%, more preferably less than 0.3%, based on the weight of the monomers. According to a particular embodiment, it is at least equal to 0.005%, more preferably at least equal to 0.01%, more preferably at least equal to 0.05%, based on the weight of the monomers.

[0084] As mentioned above, the structured polymer is obtained by inverse emulsion. The structured polymer is formed in droplets of the hydrophilic phase containing the monomers, thereby producing a polymer microgel.

[0085] Inverse emulsion

[0086] Emulsions consist of a turbid two-phase medium. In the absence of surfactants (surfactants include oil-in-water emulsifiers and water-in-oil emulsifiers), emulsions may be unstable. Under stirring, particles dispersed in water or oil can be observed, and their size distribution is wide, and the average value may be around one micron. During emulsion polymerization, monomers are dispersed in large emulsion droplets (about 1μm to 10μm in diameter) and small emulsifier micelles (about 5 to 10nm in diameter).

[0087] This polymerization technique, in particular the inverse emulsion technique, is well known to those skilled in the art. It consists in emulsifying a hydrophilic phase comprising monomers and a crosslinking agent in a lipophilic phase. This emulsification is carried out using a water-in-oil emulsifier.

[0088] Inverse emulsions generally include at least:

[0089] - a hydrophilic phase comprising monomers and a crosslinker;

[0090] - lipophilic phase;

[0091] - at least one water-in-oil emulsifier;

[0092] - at least one oil-in-water emulsifier.

[0093] Inverse emulsions consist of droplets (hydrophilic phase) dispersed in a lipophilic phase.

[0094] In the present invention, the term "water-in-oil emulsifier" refers to a compound capable of emulsifying water in oil, while "oil-in-water emulsifier" refers to a compound capable of emulsifying oil in water. It is generally believed that water-in-oil emulsifiers are surfactants with an HLB (hydrophile-lipophile balance) strictly less than 8, while oil-in-water emulsifiers are surfactants with an HLB greater than or equal to 10. Surfactants with an HLB between 8 and 10 are considered wetting agents. If necessary, those skilled in the art can refer to Chapter 11 of the Handbook of Applied Surface and Colloid Chemistry by K. Holmberg.

[0095] The hydrophile-lipophile balance (HLB) of a compound is a measure of its hydrophilicity and / or lipophilicity, determined by calculating the values ​​for different segments of the molecule, as described by Griffin in 1949.

[0096] In the present invention, we adopted Griffin's method, which calculates values ​​based on the chemical groups of the molecule. Griffin assigned a dimensionless value between 0 and 20 to provide information about water solubility and oil solubility.

[0097] The HLB value of a substance having a total molecular weight M and a hydrophilic part of molecular weight Mh is given by the following formula:

[0098] HLB=20(Mh / M)

[0099] The lipophilic phase of the inverse emulsion can be mineral oil, vegetable oil, synthetic oil or a mixture of several oils.

[0100] Examples of the mineral oil include mineral oils containing aliphatic, naphthenic, paraffinic, isoparaffinic, cycloparaffinic or naphthyl saturated hydrocarbons.

[0101] Examples of synthetic oils are hydrogenated polydecene or hydrogenated polyisobutylene, and esters such as octyl stearate or butyl oleate. The product range fits perfectly.

[0102] The solvent of the hydrophilic phase of the inverse emulsion is preferably water.

[0103] Generally speaking, during the polymerization process, the weight ratio of the hydrophilic phase to the lipophilic phase of the inverse emulsion is preferably between 50 / 50 and 90 / 10, more preferably between 70 / 30 and 80 / 20.

[0104] Preferably, the inverse emulsion contains at least one water-in-oil emulsifier selected from the group consisting of sorbitol extracts, such as sorbitan monooleate or sorbitan polyoleate, sorbitan isostearate or sorbitan sesquioleate, polyethoxylated sorbitol esters, diethoxylated cetyl alcohol, tetraethoxylated dodecyl acrylate, condensation products of fatty alcohols higher than ethylene (such as the reaction product of oleyl alcohol and 2 units of ethylene oxide), condensation products of alkylphenols and ethylene oxide (such as the reaction product of nonylphenol and 4 units of ethylene oxide), or combinations thereof. Ethoxylated fatty amines (such as 511), betaine products and ethoxylated amines and mixtures thereof can also be used as emulsifiers.

[0105] Generally speaking, the weight of the water-in-oil emulsifier in the inverse emulsion accounts for 0.1% to 10% of the total weight of the inverse emulsion.

[0106] Preferably, the inverse emulsion may contain a stabilizer. For example: a polyester having a molecular weight between 1000 and 3000 g / mol, a condensation product of polyisobutylene succinic acid or its anhydride and polyethylene glycol, wherein the molecular weight of the water-soluble block polymer is between 2500 and 3500 g / mol, for example Name of the product being sold.

[0107] Generally speaking, the inverse emulsion comprises 0.1 to 10% (by weight) of stabilizer relative to the total weight of the inverse emulsion.

[0108] The oil-in-water emulsifier is preferably selected from ethoxylated nonylphenol, preferably having 4 to 10 ethoxy groups (i.e., the degree of ethoxylation is preferably between 4 and 10); ethoxylated / propoxylated alcohols, preferably ethoxylated / propoxylated alcohols having 12 to 25 carbon atoms; ethoxylated tridecanol; ethoxylated / propoxylated fatty alcohols; ethoxylated sorbitol esters (preferably having 20 molar equivalents of ethylene oxide); polyethoxylated sorbitol laurate (preferably having 20 molar equivalents of ethylene oxide); polyethoxylated castor oil (preferably having 40 molar equivalents of ethylene oxide); decaethoxylated oleyl alcohol; heptadecyl lauryl alcohol; polyethoxylated sorbitol monostearate (preferably having 20 molar equivalents of ethylene oxide); polyethoxylated alkylphenols (preferably having 10 molar equivalent of ethylene oxide) hexadecyl ether; polyethylene oxide alkyl aryl ether; N-hexadecyl-N-ethylmorpholine ethanesulfonate; sodium lauryl sulfate; condensation products of fatty alcohols and ethylene oxide (preferably with 10 molar equivalents of ethylene oxide); condensation products of alkylphenols and ethylene oxide (preferably with 12 molar equivalents of ethylene oxide); condensation products of fatty amines and 5 or more molar equivalents of ethylene oxide (preferably 5 to 50 molar equivalents); ethoxylated tristyrylphenol; condensation products of ethylene oxide and partially esterified polyols with fatty chains and their anhydrous forms; amine oxides, preferably alkyl polyglucosides; glucose amides; phosphates; alkylbenzene sulfonic acids and salts thereof; and surfactant water-soluble polymers. The water-in-oil emulsifier can also be a mixture of one or more water-in-oil emulsifiers. The alkyl group of the oil-in-water emulsifier refers to a straight chain or branched chain group, preferably having 1 to 20 carbon atoms, more preferably 3 to 15 carbon atoms. In addition, the aryl group of these oil-in-water emulsifiers preferably has 6 to 20 carbon atoms, more preferably 6 to 12 carbon atoms and mixtures thereof.

[0109] Generally speaking, the weight of the oil-in-water emulsifier in the inverse emulsion is between 0.01 and 10% relative to the total weight of the inverse emulsion.

[0110] Generally speaking, the concentration of the polymer microgel in the inverse emulsion is between 5 and 65%, preferably between 20 and 50%, relative to the total weight of the inverse emulsion.

[0111] The polymerization of monomers is a free radical polymerization, which includes polymerization using ultraviolet light initiators, azo initiators, redox initiators or thermal initiators.

[0112] The polymerization initiator can be selected from compounds that dissociate into free radicals under polymerization conditions, such as organic peroxides, hydroperoxides, hydrogen peroxide, persulfates, azo compounds and redox catalysts. It is best to use a water-soluble initiator. In some cases, it is best to use a mixture of various polymerization initiators, such as a mixture of a redox catalyst and an azo compound.

[0113] In a preferred embodiment of the present invention, the polymer microgel is prepared by polymerization of monomers in an inverse microemulsion.

[0114] The method for preparing the reverse microemulsion can be the same as the method described in the document "Application of the Cohesive Energy Ratio Concept (CER) in the Formation of Polymerizable Microemulsions" by C. Holtzscherer and F. Candau (Vol. 29, No. 4, 1988, pp. 411-423).

[0115] The goal is to reach the thermodynamically stable critical value of the water phase / lipophilic phase / surfactant ternary. This will form a transparent, mobile microemulsion.

[0116] Microemulsions can also be obtained by providing mechanical energy to reduce the droplet size of the hydrophilic phase of the emulsion to between 20 nm and 500 nm, preferably between 50 nm and 250 nm, more preferably between 80 nm and 150 nm.

[0117] The particle size (microgel particle size) corresponds to the droplet size of the hydrophilic phase of the microemulsion. Therefore, the particle size of the microgel is between 20nm and 500nm, preferably between 50nm and 250nm, and more preferably between 80nm and 150nm.

[0118] Generally speaking, during the preparation process, the structured polymer of the microgel is in a saturated state in water, and the expansion volume in the cement-based composition cannot exceed 20%, preferably does not exceed 10%, and more preferably does not expand at all. For example, when the size of the prepared microgel is 100 nm, its size in the cement-based composition does not exceed 120 nm, preferably does not exceed 110 nm, and more preferably remains at 100 nm.

[0119] If necessary, those skilled in the art can refer to EP2802936 for information on how to produce microemulsions.

[0120] Generally speaking, the content of the structured polymer in the inverse microemulsion is between 5% and 65%, preferably between 10% and 50%, and more preferably between 15% and 40%, relative to the total weight of the inverse microemulsion.

[0121] Generally speaking, during the polymerization process, the weight ratio of the hydrophilic phase to the lipophilic phase of the reverse microemulsion is preferably between 80 / 20 and 20 / 80, more preferably between 70 / 30 and 30 / 70, and even more preferably between 60 / 40 and 40 / 60.

[0122] Preferably, the water-in-oil emulsifier in the reverse microemulsion is selected from sorbitan esters (such as sorbitan monooleate, sorbitan isostearate, sorbitan sesquioleate, sorbitan trioleate or a mixture thereof), oleyl diethanolamide, or a combination thereof.

[0123] Generally speaking, the weight of the water-in-oil emulsifier in the reverse microemulsion accounts for 0.01 to 10% of the total weight of the reverse microemulsion, preferably between 0.1 and 5%.

[0124] Preferably, the oil-in-water emulsifier in the reverse microemulsion can be selected from the following group: ethoxylated sorbitol esters, such as ethoxylated sorbitol oleate containing 20 moles of ethylene oxide, ethoxylated sorbitol hexaoleate, decaethoxylated oleyl hexadecyl alcohol, nonylphenol containing 10 moles of ethylene oxide (10EO), polyethoxylated sorbitol hexaoleate, or a combination thereof.

[0125] Generally speaking, the weight of the oil-in-water emulsifier in the reverse microemulsion accounts for 0.1% to 20% of the total weight of the reverse microemulsion, preferably 0.5% to 15%.

[0126] According to the present invention, the size of the microemulsion droplets (hydrophilic phase) is between 20 nm and 500 nm, preferably between 50 nm and 250 nm, and more preferably between 80 nm and 150 nm.

[0127] By "size of the microemulsion droplets" is meant the average size of a population of droplets. This size corresponds to the average diameter measured, preferably using a laser measuring device, using conventional techniques that are part of the knowledge of a person skilled in the art. A device of the Zetasizer Nano type from Malvern may be used.

[0128] Cementing technology

[0129] The present invention also relates to a cementing process, which comprises injecting a cement-based composition into an underground rock formation. In this process, the cement-based composition comprises a polymer microgel, which contains at least one structured polymer obtained by polymerizing monomers in an inverse microemulsion.

[0130] In other words, more specifically, the method according to the present invention comprises the following steps:

[0131] - preparing a cementitious composition comprising a polymer microgel, wherein the polymer microgel comprises:

[0132] (i) at least one structured polymer, wherein the structured polymer is obtained by polymerizing monomers in an inverse microemulsion,

[0133] (ii) cement,

[0134] (iii) water, and

[0135] (iv) optionally at least one cement additive;

[0136] - injecting the cement-based composition into a borehole containing a casing forming an annular space between the casing and the borehole, so as to perform cementing through the casing and / or in the annular space around the casing and / or in the openings below the casing.

[0137] As mentioned above, one of the advantages of the present invention compared to the prior art is that cementing can be performed without being affected by temperature while ensuring good performance and without the risk of cracks.

[0138] After the microgel is injected into the borehole, it remains in the form of particles. It does not dissolve, nor does it solubilize. It remains in an undissolved state, and its size does not change by more than 20% of the volume in the borehole, preferably by less than 10% of the volume, and more preferably it does not change in the cement-based composition or in the borehole. For example, when the size of the microgel after preparation is 100nm, its size in the cement-based composition and in the borehole does not exceed 120nm, preferably does not exceed 110nm, and more preferably remains 100nm.

[0139] The microgel does not hydrolyze within the drilled hole.

[0140] Generally speaking, the temperature in the borehole is at least 50°C, preferably at least 70°C, more preferably at least 90°C, and even more preferably at least 100°C.

[0141] The invention and the advantages described will become better apparent from the following non-limiting examples given for the purpose of illustrating the invention. Example

[0142] Listed below are the abbreviations used in the following examples:

[0143] AMD: Acrylamide

[0144] ATBS: 2-Acrylamido-2-methylpropane sulfonic acid

[0145] PVA: Polyvinyl alcohol

[0146] SB rubber: styrene butadiene rubber

[0147] MBA: Methylene bisacrylamide

[0148] MBS: Sodium metabisulfite

[0149] Synthesis of polymer microgels via inverse emulsion polymerization

[0150] The aqueous phase was prepared from 680 g of ATBS.Na (sodium 2-acrylamido-2-methylpropane sulfonate, 50% by weight in water), 0.2 g of MBA and 0.2 g of Versenex 80.

[0151] The oil phase consists of 234.5 g oil ( D100 S) and 25g tall oil fatty acid diethanolamine as a water-in-oil emulsifier.

[0152] While stirring, the aqueous phase was added to the oil phase to form an emulsion. With the temperature stabilized at 25°C, nitrogen was bubbled through the resulting dispersion for 30 minutes, then 0.1 g of tert-butyl hydroperoxide was added to the emulsion, and 5 g of a solution containing 0.75 g of MBS was added to the dispersion at a rate of 0.1 ml per minute. The polymerization reaction was carried out at a temperature of 38°C to 42°C and lasted for about 90 minutes. 5 grams of a solution containing 0.3 g of MBS was added at a flow rate of 1.0 ml per minute to capture residual monomers. A water-in-oil polymer emulsion was obtained, in which the weight content of polymer 1 was 20%.

[0153] Add 50g of water-in-oil emulsifier ( NP 8, nonylphenol ether and polyethylene glycol 8OE) were used for the emulsion (percentages are expressed by weight relative to the weight of the inverse emulsion). The resulting water-in-oil polymer emulsion contained 34% (by weight) of polymer 1.

[0154] Synthesis of polymer microgels via precipitation polymerization

[0155] The reactor used for the polymerization was a 2 L jacketed stirred vessel equipped with a distillation column, a pH probe, a thermometer, a strong stirrer, a nitrogen bubbling nozzle, and an ammonia inlet.

[0156] First, 1570 g of pure tert-butyl alcohol (2-methyl-2-propanol) and 65 g of water were added to the reactor. Then, 112 g of the acid ATBS were added under stirring. The monomers were then completely neutralized by a stream of gaseous ammonia flowing through the suspension until a pH value of 8 was reached. The ammonia feed was then stopped and 1.3 g of MBA was added. The solution was then sparged with nitrogen for one hour while the temperature was raised to 55°C.

[0157] When the temperature stabilized at 55°C, 1.6 g of dibenzoyl peroxide was added to the solution to start the reaction and precipitate the formed polymer. After the temperature stopped rising, the solvent was evaporated under vacuum to directly obtain a dry powder, namely polymer 2.

[0158] The polymer microgels were synthesized by inverse microemulsion polymerization.

[0159] In a 1L reactor, 440g of ATBS (50% by weight in water) and 0.22g of MBA were mixed. The pH of the solution was adjusted to 6.5 with a few drops of concentrated sulfuric acid. Then 440g of isoparaffin oil, 12.3g of sorbitan oleate and 107.7g of ethoxylated sorbitan caproate were added. The mixture was then stirred to make it transparent and uniform. The stirring speed was maintained at 200rpm during 25 minutes of degassing with nitrogen. Concentrated cumene hydroperoxide was then added to the culture medium, followed by 1ml of sodium metabisulfite (10% by weight in water). The mixture was placed in a nitrogen environment for polymerization. The reaction was exothermic and the temperature rose to 50°C within 1 minute. After the polymerization was completed, 0.2g of MBS (40% by weight in water) was added to remove residual monomers. The obtained product was transparent and had a low viscosity (24cP), corresponding to polymer 3.

[0160] As shown in Table 2, different polymers (4-7) were synthesized by changing different parameters (composition and size of polymer microgels) using the same method.

[0161] Preparation of cement-based compositions

[0162] The cement-based composition was prepared by mixing the ingredients listed in Table 1 in a mixing bowl with a capacity of 1 L and equipped with a blade. The ingredients were added over 15 seconds at a rotation speed of 4000 rpm and then stirred at a rotation speed of 12000 rpm for 35 seconds.

[0163] Retarder (sodium lignin sulfonate) and dispersant (sodium naphthalene sulfonate) are used in the preparation of slag cement.

[0164]

[0165] Table 1: Slag cement formula (44% / cement means 44 parts by weight per 100 parts by weight of cement).

[0166] As mentioned above, the Static Gel Strength Analyzer (SGSA) uses acoustic attenuation to evaluate the gelation of cement slurries under specified conditions of temperature and pressure. The device measures the static gel strength (SGS) and resistance to compression as a function of time. In other words, the device evaluates the gelation of cement during the dehydration process, which occurs after the cement slurry is placed in the well. At this stage, the goal is to ensure that the setting time is as short as possible to prevent gas migration through the cement column. From the beginning of gelation (when the SGS reaches 100lb / 100ft 2 ) to the end of the gas migration risk (more than 500lb / 100ft 2 ) must be less than 45 minutes. Therefore, in the following example the measured transition period is between 100 and 500 lb / 100 ft 2When the solidification time exceeds 60 minutes, the test is stopped.

[0167] The equipment used was a Chandler Engineering brand and was specifically designed to measure the transition period of a fluid in the presence and absence of a gas migration inhibitor.

[0168] The grout conditioning was carried out at ambient temperature, 70°C or 90°C for 30 minutes with an applied pressure of 3,000 PSI. The formulation used was the same as in Table 1, with a polymer component weight percentage of 0.42%.

[0169]

[0170]

[0171] Table 2: Illustrative compositions of the invention (INV) or comparative tests (CE) (EMI: inverse emulsion; μ-EMI: inverse microemulsion; PP: precipitation)

[0172] In Table 2, the particle size corresponds to the droplet size of the hydrophilic phase in the emulsion or microemulsion.

[0173] The structured polymers (polymers 3-4 and 6-7) and microgels obtained by the reverse microemulsion method have better properties than those obtained by the alternative synthesis method (polymers 1 and 2). They have a shorter transition period than microgels prepared from microemulsions with hydrophilic phase droplets larger than 500 nm (polymers 4 and 6 compared to polymers 1 and 5).

[0174] The concentration of the polymer of the present invention is greatly reduced, and the amount of styrene-butadiene rubber must be multiplied by more than 7.5 times to obtain performance that is even comparable to that of the microgel of the present invention (Polymer 6 compared with Comparative Example CE6), while for the polyvinyl alcohol latex compound, it is multiplied by more than 4.5 times (Polymer 5 compared with Comparative Example CE7).

[0175] Polyvinyl alcohol latex compounds exhibit insufficient performance at temperatures exceeding 90°C even at high concentrations, whereas the microgel of the present invention is not affected by temperature.

Claims

1. A cement-based composition comprising - polymer microgels; -cement; - Water; and - optionally at least one cement additive; in, The polymer microgel contains at least one polymer structured by at least one crosslinking agent, wherein the structured polymer is obtained by polymerization in an inverse microemulsion of at least one monomer, The microemulsion contains hydrophilic phase droplets with a size between 20 and 500 nm.

2. The cement-based composition according to claim 1, characterized in that The structured polymer comprises at least one anionic monomer and optionally at least one nonionic monomer.

3. The cement-based composition according to claim 2, characterized in that At least one of the anionic monomers has a functional group selected from acrylic acid, maleic acid, fumaric acid, malonic acid, itaconic acid, and allyl functional groups.

4. The cement-based composition according to claim 2 or 3, characterized in that The anionic monomer is 2-acrylamido-2-methylpropanesulfonic acid and / or a salified form thereof.

5. The cement-based composition according to any one of claims 1 to 4, characterized in that The structured polymer comprises at least 30 mol % of at least one anionic monomer.

6. The cement-based composition according to claim 2, characterized in that The nonionic monomer is selected from the following group: acrylamide, methacrylamide, N-isopropylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, N-hydroxymethylacrylamide, N-vinylformamide (NVF), N-vinylacetamide, N-vinylpyridine and N-vinylpyrrolidone (NVP), N-vinylimidazole, N-vinylcaprolactam, N-vinylsuccinimide, acryloylmorpholine (ACMO), acryloyl chloride, glycidyl methacrylate, glyceryl methacrylate, diacetone acrylamide, C1-C3 alkyl hydroxyalkyl (meth) acrylate, C1-C3 alkyl aminoalkyl (meth) acrylate, C1-C3 alkyl sulfoalkyl (meth) acrylate, or a combination thereof.

7. The cement-based composition according to any one of claims 1 to 6, characterized in that The crosslinking agent is a monomer having at least two unsaturated olefinic bonds.

8. The cement-based composition according to any one of claims 1 to 7, characterized in that The structured polymer comprises less than 5% by weight of a crosslinking agent relative to the weight of the monomers.

9. The cement-based composition according to any one of claims 1 to 8, characterized in that The cementitious composition comprises 100 to 100,000 ppm by weight of the polymer microgel.

10. A cementing process comprising the following steps: - preparing a cementitious composition according to any one of claims 1 to 9; - injecting the cementitious composition into a borehole provided with a casing defining an annular space between the casing and the borehole, so as to perform cementing through the casing and / or in the annular space around the casing and / or in an opening below the casing.

11. Use of polymer microgel, characterized in that: For forming a cementitious composition, the polymer microgel comprises at least one polymer structured by at least one crosslinking agent; The structured polymer is obtained by polymerization in an inverse microemulsion of at least one monomer; The microemulsion comprises hydrophilic phase droplets with a size between 20 and 500 nm.

12. A method for preparing a cement-based composition, characterized in that: The composition contains a mixture of the following compounds: - polymer microgels; -cement; -water; and - optionally at least one cement additive; wherein the polymer microgel contains at least one polymer structured by at least one crosslinking agent, wherein the structured polymer is obtained by polymerization in an inverse microemulsion of at least one monomer, The microemulsion contains hydrophilic phase droplets with a size between 20 and 500 nm.

Citation Information

Patent Citations

  • Novel chemically crosslinked polyvinyl alcohol (PVA), its synthesis process and its applications as a filtrate control agent in petroleum fluids.

    FR2704219A1

  • NEW SULFOBETAINE MONOMERS, PREPARATION PROCESS AND THEIR USES

    FR3104578A1

  • Hydrated crystalline form of 2-acrylamido-2-methylpropane sulfonic acid

    US10759746B2

  • Additive including cross-linked polycarboxylic copolymer and cement composition comprising the same

    US20150203402A1

  • Styrene-butadiene interpolymer latex based cement additives containing a silane

    US4151150A

Cited By

  • Preparation method of special admixture for reservoir rockfill self-compacting concrete

    CN121974596A

  • Preparation method of special admixture for reservoir rockfill self-compacting concrete

    CN121974596B